Genetic analysis of postoperative recurrence of pancreatic cancer potentially owing to needle tract seeding during EUS-FNB - Kawabata, Hidemasa; Miyazawa, Yuki; Sato, Hiroki; Okada, Tetsuhiro; Hayashi, Akihiro; Iwama, Takuya; Fujibayashi, Shugo; Goto, Takuma; Sasajima, Junpei; Takauji, Shuhei; Fujiya, Mikihiro; Torimoto, Yoshihiro; Tanino, Mishie; Omori, Yuko; Ono, Yusuke; Karasaki, Hidenori; Mizukami, Yusuke; Okumura, Toshikatsu (Endoscopy International Open, 2019)
Background and study aims Needle tract seeding during endoscopic ultrasound fine-needle biopsy (EUS-FNB) remains a concern. We investigated whether such seeding occurred in a patient with pancreatic ductal adenocarcinoma (PDA).Patient and methods Surgically resected and EUS-FNB-derived specimens were genotyped to determine if a gastric wall tumor that emerged 3 years after curative resection of an early-stage PDA was clonally related to the original tumor. Results The gastric tumor histologically resembled the primary PDA; the lesions also shared KRAS, SMAD4, and RNF43 mutations. Genotyping of the preoperative EUS-FNB specimen, in which cancer was not detected, nevertheless revealed mutations that were identical to those in the resected primary and recurrent tumors. While the primary PDA had a low frequency of mutant SMAD4, such mutations were highly prevalent in both the EUS-FNB and recurrent tumor specimens. Conclusions The genetic lineages of sampled tissues from our patient revealed that needle tract seeding may have incidentally occurred when a subset of neoplastic cells within a heterogeneous tumor (i. e., an aggressive clone) was targeted during EUS-FNB.